EKSPERIMENTASI MODEL PEMBELAJARAN BERBASIS MASALAH DAN MODEL PEMBELAJARAN KOOPERATIF TIPE STAD DENGAN PENDEKATAN SAINTIFIK DITINJAU DARI KEMANDIRAN BELAJAR - Brilliyanti, Fanny; Usodo, Budi; Subanti, Sri (Jurnal Pembelajaran Matematika, 2016)
Abstract: The aims of this research were to know: (1) which one gives better mathematics achievement, cooperative learning model Student Teams Achievement Division (STAD), model Problem Based Learning (PBL), or model classical with scientific approach;  (2) which one has better mathematics achievement, students who have high, medium, or low of self regulated learning; (3) for each learning model, which one has better  mathematics achievement, students who have high, medium, or lowof self regulated learning; (4) For each category of self regulated learning, which one gives better mathematics achievement, STAD, PBL, or classical with scientific approach. The populations were all students of Junior High School in Surakarta City. Sampling was done by stratified cluster random sampling. The samples were students of SMP N 2 Surakarta, SMP N 15 Surakarta and SMP N 24 Surakarta. The instruments used were mathematics achievement tests and self regulated learning questionnaire. The data was analyzed using unbalanced two-ways anova. The conclusion were as follows. (1) PBL with scientific approach gives better mathematics achievement than STAD with scientific approach, and STAD with scientific approach and classical with scientific approach have the same mathematics achievement. (2) Mathematics achievement of students who have high self regulated learning was better than students who have medium and low self regulated learning and students who have medium self regulated learning was better than students who have low self regulated learning (3) For STAD and PBL with scientific approach, students who have high and medium self regulated learning have the same mathematics achievement. Mathematics achievement of students who have high self regulated learning was better than students who have low self regulated learning. Students who have medium and low self regulated learning have the same mathematics achievement. For classical with scientific approach, students who have high, medium, and low self regulated learning have the same mathematics achievement. (4) For students who have high self regulated learning, STAD with scientific approach gives the same mathematics achievement with PBL and classical with scientific approach but PBL with scientific approach gives better mathematics achievement than classical with scientific approach. For students who have medium and low self regulated learning, all learning models give the same mathematics achievement.Keywords: Student Team Achievment Division (STAD), Problem Based Learning (PBL), classical, scientific approach, self regulated learning (SRL)